ENGINEERING PEDAGOGY AS A BASIS FOR STAFFING OF HIGHER TECHNICAL EDUCATION - Vyacheslav M. Prikhod’Ko; Alexandr N. Solovyev (Высшее образование в России)
We generalize the experience of technical teachers training and certification implemented by International Society for Engineering Education IGIP in parallel with the activity of the recent created by the European Commission «High Level Group on the modernization of higher education». We use some theses on the internationalization of higher education teachers training in the European Higher Education Area adopted by this Group. We propose to apply this mutual experience in the implementation of the Presidential Programdirected on the technicians and engineers training in the Russian Federation.